Heat transport in phononic-like membranes: Modeling and comparison with modulated nano-wires. (November 2017) - Verdier, Maxime; Lacroix, David; Termentzidis, Konstantinos
Highlights: The thermal conductivity of nano-structured silicon is computed by MD & MC. Nanowires and nanoporous phononic-like membranes thermal conductivity are compared. The two systems have different conductivities for same characteristic length. Orientation of the phonon scattering surfaces influences the thermal properties. Abstract: The thermal conductivity of phononic-like membranes and their analogous nano-wires are computed with both Molecular Dynamics and Monte Carlo simulations. Using both methods, the thermal conductivity of the porous membranes with cylindrical pores is found to be lower than the nano-wire's one for the same scattering surface to volume. This work confirms experimental observations by Nomura et al. (2015) and Yu et al. (2010) for similar systems. The lower thermal conductivity of membranes is attributed to the different orientation of the scattering surfaces either at the pores or at free surfaces and not to coherent effects. The comparison between the porous membranes and nano-wires with periodic cylindrical modulations shows that thermal transport is hindered further when there are surfaces perpendicular to the heat flow. These results show that coherent effects have no impact on thermal transport in both kind of nano-structures at room temperature.